Tarqiyyatu Mahārati al-Kalāmi bi Ṯiqqati al-Nafsi fī Barnāmiji al-Khaṭābah al-‘Arabiyyah fī al-Madrasah al-Thānawiyyah al-Islāmiyyah Walisongo Gending Probolinggo: Enhancing Speaking Skills Through Self-Confidence in the Arabic Oratory Program at Walisongo Islamic Senior High School Gending Probolinggo - Abicandra, Muh. Nidom Hamami; Hidayati, Siti Nur (Critical Review of English-Arabic World Journal, 2024)
الخطابة هي التعبير الشفوي من خلال إلقاء الأفكار بصورة الكلام في الأماكن العامة أو الإلقاء لتقديم الأراء، وتطلب الثقة بالنفس، مع أنها تجعل النفس القدرة والفخر بما يفعله بشكل إيجابي في تحسين مهارة الكلام. المدرسة الثانوية الإسلامية واليسونغو كندينغ إحدى المدارس التي قامت بتنفيذ برنامج الخطابة كل شهر. هذا البرنامج لترقية مهارة الكلام لدى الطلاب بثقة النفس. تهتم الباحثة بمعرفة المزيد عن برنامج الخطابة، وبالتلي تريد الباحثة هنا جعل الجيل القادم أكثر شجاعة وثقة. يهدف هذا البحث إلى ما يلي: وصف ترقية مهارة الكلام بثقة النفس في برنامج الخطابة العربية في المدرسة الثانوية الإسلامية واليسونغو كندينغ برابالنجا ووصف مدى ترقية مهارة الكلام بثقة النفس في برنامج الخطابة العربية في المدرسة الثانوية الإسلامية واليسونغو كندنيغ برابالنجا. استخدم هذا البحث المدخل الكيفي بالطريقة الوصفية. وأما طريقة جمع البيانات فهي الملاحظة، والمقابلة الشخصية، والتوثيق، وتم تحليل البيانات من خلال تخفيض البيانات، وعرض البيانات، الاستنتاج. أما نتائج هذا البحث فهي أن ترقية مهارة الكلام بثقة النفس في برنامج الخطابة العربية في المدرسة الثانوية الإسلامية واليسونغو كندينغ برابالنجا هو يتضمن تنفيذ تحسينها على ثلاثة أنشطة مهمة، وهي الأنشطة الأولى، الأنشطة الأساسية، الأنشطة الختامية. ومدى ترقية مهارة الكلام بثقة النفس في برنامج الخطابة العربية في المدرسة الثانوية الإسلامية واليسونغو كندينغ برابالنجا هو تم تنفيذها 24 عاما تقريبا بما أن الطلاب يقدرون على ترقية مهارتهم في الكلام بعد أن تكون لديهم الثقة بالنفس في برنامج الخطابة.   Oratory (public speaking) is a form of verbal expression through delivering ideas orally in public places or presenting opinions. It requires self-confidence, as it gives individuals a sense of ability and pride in what they do, which positively contributes to improving speaking skills. Al-Walisongo Islamic Senior High School in Kending is one of the schools that conducts a monthly oratory program. This program aims to enhance students’ speaking skills with confidence. The researcher is interested in learning more about the oratory program and, consequently, aims to help the next generation become more courageous and confident. The objectives of this study are as follows: to describe the improvement of speaking skills with self-confidence in the Arabic oratory program at Al-Walisongo Islamic Senior High School in Kending, Prabalangga, and to describe the extent to which speaking skills with self-confidence are improved in this program. This research uses a qualitative approach with a descriptive method. Data collection methods include observation, interviews, and documentation, and the data were analyzed through data reduction, data display, and conclusion drawing. The results of this study show that the improvement of speaking skills with self-confidence in the Arabic oratory program at Al-Walisongo Islamic Senior High School in Kending, Prabalangga, involves three main stages: preliminary activities, core activities, and concluding activities. The extent of improvement in speaking skills with self-confidence in this program has been achieved for approximately 24 years, as students have been able to develop their speaking skills once they gained self-confidence through the oratory program.